2012
DOI: 10.1039/c2jm30621b
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous titanate nanospheres fabricated using a contactless phase change process

Abstract: Nanometre-sized spherical glasses without conventional networkforming oxides were fabricated for the first time using a novel contactless phase change process. The as-fabricated titanate nanomaterials possess perfect spherical shape and superior optical properties such as high refractive index and wide-banded transmittance from 250 nm to 11 mm. We believe that these unique nanospheres may find significant applications such as antireflective coatings for photovoltaic devices, and the synthesis approach can be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…After the laser power was turned off, the homogeneous melts of NLZ1-4 and NLZ6-9 were quenched into transparent solid spherical glasses with a diameter size of ~3 mm at an approximate cooling rate of 250 ℃/s. The details about ADL furnace have been introduced elsewhere [24,25]. A video camera with high-resolution charge-coupled device was applied to realize the magnified in situ observation of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…After the laser power was turned off, the homogeneous melts of NLZ1-4 and NLZ6-9 were quenched into transparent solid spherical glasses with a diameter size of ~3 mm at an approximate cooling rate of 250 ℃/s. The details about ADL furnace have been introduced elsewhere [24,25]. A video camera with high-resolution charge-coupled device was applied to realize the magnified in situ observation of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Shift current is yet another dominant mechanism in bulk BTO as photocurrent does not only depend on the magnitude of material polarization, but also on electronic states with delocalized, covalent 4 bonding that is highly asymmetric along the current direction [13]. However, nanometer-sized BTO glass has wider transmittance window 250 nm -11,000 nm and high refractive index ~ 2.15 which offers lower reflectance to the Si based photovoltaic devices [14]. Amorphous BTO thin films of 140 nm thick deposited using metalorganic chemical vapor deposition was reported to show high optical transmittance of 80 % with optical band gap of 4.71 eV in the visible wavelength range [15].…”
Section: Introductionmentioning
confidence: 99%
“…Under these circumstances, the melt can transform into glass. In our previous works, TiO 2 ‐ and Nb 2 O 5 ‐based glasses with high index of refraction have been successfully fabricated by a containerless method, and exhibit excellent optical properties from the network former‐free glasses. According to the reference, it is found that TiO 2 ‐based bulk glasses doped with different rare‐earth elements can emit intense upconversion luminescence …”
Section: Introductionmentioning
confidence: 99%